2012
DOI: 10.1021/ja211417g
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Zn2+Binding to Cys2His2and Cys2HisCys Zinc Fingers and a Cys4Transcription Factor Site

Abstract: The thermodynamics of Zn(2+) binding to three peptides corresponding to naturally occurring Zn-binding sequences in transcription factors have been quantified with isothermal titration calorimetry (ITC). These peptides, the third zinc finger of Sp1 (Sp1-3), the second zinc finger of myelin transcription factor 1 (MyT1-2), and the second Zn-binding sequence of the DNA-binding domain of glucocorticoid receptor (GR-2), bind Zn(2+) with Cys(2)His(2), Cys(2)HisCys, and Cys(4) coordination, respectively. Circular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
89
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 60 publications
10
89
0
Order By: Relevance
“…Since ligand pKa values are not known, the total number of protons that are displaced upon metal binding (a + 2b in Scheme 1) cannot be calculated using the approach described above. An alternate method [73,74], which takes advantage of the change in ΔH HB if the experimental buffer is altered, has been widely used in ITC experiments [4,10,11,24,26,41,75]. Practically, this strategy requires multiple titrations to be carried out at the same pH in at least three different buffers under otherwise identical experimental conditions.…”
Section: Metal-protein Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since ligand pKa values are not known, the total number of protons that are displaced upon metal binding (a + 2b in Scheme 1) cannot be calculated using the approach described above. An alternate method [73,74], which takes advantage of the change in ΔH HB if the experimental buffer is altered, has been widely used in ITC experiments [4,10,11,24,26,41,75]. Practically, this strategy requires multiple titrations to be carried out at the same pH in at least three different buffers under otherwise identical experimental conditions.…”
Section: Metal-protein Interactionsmentioning
confidence: 99%
“…As such, only indirect experiments that rely on competition with another metal ion or spectroscopic probe can be used to investigate Zn 2+ -protein interactions. Alternatively, Zn 2+ binding events are characterized by a quantifiable heat signature which can be exploited by ITC to gain insight into Zn 2 + -dependent systems such as zinc finger domains [4][5][6][7], carbonic anhydrase [8][9][10], and insulin [11]. Additionally, ITC has played a role in understanding countless important bioinorganic systems including ferritin and transferrin [12][13][14][15][16][17], amyloid beta [18,19], nucleases [20][21][22][23] and cardiac troponin C [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study using ITC to quantify the thermodynamics of Zn 2+ binding to peptides corresponding to three naturally occurring Zn-binding sequences in transcription factor proteins supported these early findings and concluded that zinc binding to the classical Cys 2 His 2 zinc finger is both enthalpically and entropically favored but less so (i.e. more enthalpically disfavored and entropically favored with increasing Cys ligands) with two derivatives containing three Cys and one His (Cys 2 HisCys) or four Cys (Cys 4 ) metal coordinating residues (21). Additionally, the study found that upon binding, Zn 2+ displaces a proton from each coordinated Cys residue negating the notion that Cys thiols in zinc fingers and corresponding proteins remain protonated upon Zn 2+ binding.…”
Section: Chemical Biochemical and Binding Properties Of Essential Fimentioning
confidence: 81%
“…This trend is attributed to an increased enthalpic penalty to deprotonate the thiols of peptide with increasing number of cysteines. This is accompanied by a concomitant entropic gain due to protons release and this enthalpic-entropic compensation process is perhaps a common feature of tetrahedral Zn 2+ coordination in these types of peptides (21). …”
Section: Chemical Biochemical and Binding Properties Of Essential Fimentioning
confidence: 99%